An analytical assessment of credit card fraud detection techniques: Supervised, Unsupervised, and Reinforcement Learning - Abdourahman Djamal Djama (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Bank card fraud is an increasingly serious problem for individuals, businesses and financial institutions. There is a need for effective fraud detection measures to protect consumers and businesses from financial losses. Method. information-theoretical analysis of methods for detecting fraud with bank cards, machine learning algorithms in improving the accuracy of fraud detection. Result. An analytical evaluation of fraud detection methods is provided, covering different learning approaches: supervised, unsupervised and reinforcement learning. Conclusion. The choice of a fraud detection method should be based on an understanding of the available data, the specific requirements of the application domain and the trade-offs between methods in terms of performance, adaptability and computational complexity.